Supervisor support, role ambiguity and productivity associated with presenteeism: a longitudinal study - Zhou, Q. (2016)
Integrating the social informational processing perspective and conservation of resources theory, we proposed and examined the impact of supervisor support and role ambiguity on productivity associated with presenteeism and the mediating effect of role ambiguity on the link between supervisor support and productivity associated with presenteeism. The results based on the longitudinal data from 99 employees from an IT consulting company showed that role ambiguity was negatively related to productivity associated with presenteeism (SPS-6). In contrast, supervisor support indirectly influenced productivity associated with presenteeism via reducing role ambiguity.